Theoretical grounds of workshop on patient communication using Gestalt psychotherapy approach - Ogórek-Tęcza, Beata (Nursing Problems / Problemy Pielęgniarstwa, 2025)
Theoretical grounds of a workshop program are based on a review of the most important principles of being in a relationship as well as on referring to specific contexts of exercises, based on theoretical concepts of attentiveness, transference and countertransference, resonance, the role and tasks of a support person, elements of field theory, and self-disclosure in contact with the patient. All of these serve to deepen the connection with the patient, and enhance one’s skills and competencies, including self-awareness in a relationship. For the purpose of a workshop for medical students, this knowledge and its use in clinical practice increase the chances of counteracting burnout and excessive emotional costs connected with difficult situations experienced in various relationally challenging situations.